An advanced review of speech-languaje pathology - Rose-McKibbin, Celeste (Pro-ed, 2006)
The idea for the first of this book was born in 1996 was part of a team that was conducting workshops for speech-languaje pathologists who needed to pass the PRAXIS so the could become license and certified in order to accommodate increasingly profesional state and federal requirements.